How does public infrastructure construction influence CO2 emissions? A global case - Qian, Yichen; Sun, Renjin; Zhao, Jun; Song, Sasa; Wang, Pinchen (Frontiers in Environmental Science, 2022)
To empirically investigate as to whether and how public infrastructure influences the global greenhouse effect, this study utilizes a panel dataset of 35 countries over the period 2003–2019 for regression estimation. Furthermore, regional heterogeneous and mediation effects between infrastructure and carbon dioxide (CO2) emissions are explored. The primary findings insist that: 1) at the global level, public infrastructure is positive associated with CO2 emissions. In other words, strengthening infrastructure at this stage is not conducive to mitigating the greenhouse effect; 2) public infrastructure construction development in Belt and Road Initiative (BRI) countries has a greater positive impact on CO2 emissions than in non-BRI countries; and 3) the mediation roles of industrial upgrading and trade openness are established; specifically, trade openness and industrial upgrading are valid transmission routes through which public infrastructure affects CO2 emissions. Based on the above three findings, a number of policy implications related to accelerate low-carbon construction of infrastructure and promote industrial upgrading are proposed.